2022
DOI: 10.1177/10781552221098422
|View full text |Cite
|
Sign up to set email alerts
|

Erythema nodosum after azacitidine in a patient with acute myeloid leukemia

Abstract: Introduction Nodular skin lesions in patients with acute myeloid leukemia (AML) raise clinical suspicion for leukemia cutis versus fungal infections. Here, we report a rare case of treatment-related erythema nodosum (EN) in a patient with AML. Case Report Approximately 5 weeks after the initiation of sorafenib and one week after azacitidine initiation, a 32-year-old man with primary refractory AML presented with several painful red nodules on the lower extremities. Histological examination established a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…On the other hand, EN is reported with other TKIs such as imatinib, 17,18 sorafenib, 19 nilotinib, 20 ponatinib, 21 and other drugs treating leukemia (azacitidine). 28 Other types of panniculitides are also reported with malignancies and drugs. EN and Sweet syndrome share clinical similarities but can be distinguished by specific features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, EN is reported with other TKIs such as imatinib, 17,18 sorafenib, 19 nilotinib, 20 ponatinib, 21 and other drugs treating leukemia (azacitidine). 28 Other types of panniculitides are also reported with malignancies and drugs. EN and Sweet syndrome share clinical similarities but can be distinguished by specific features.…”
Section: Discussionmentioning
confidence: 99%
“…Although EN is one of the reported uncommon hypersensitivity adverse events in clinical studies and post‐marketing experience of dasatinib 27 ; no case reports were found in literature. On the other hand, EN is reported with other TKIs such as imatinib, 17,18 sorafenib, 19 nilotinib, 20 ponatinib, 21 and other drugs treating leukemia (azacitidine) 28 …”
Section: Discussionmentioning
confidence: 99%